SCANNING PROBE TECHNIQUES IN MICRO- AND NANOMECHANICS - S. A. Chizhik; S. V. Siroezhlin (Приборы и методы измерений)
Methods of materials local physics and mechanics properties estimation on the nanoscale are considered. The methods are realized on the base of AFM with surface mapping contrast, static and dynamics force spectroscopy and with the procedures of nanowear and oscillating microtribometry.